Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/jbm4.10651
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Vitamin D Supplementation and Childhood Bone Mass at Age 4 Years: Findings From the Maternal Vitamin D Osteoporosis Study (MAVIDOS) Randomized Controlled Trial

Abstract: In the Maternal Vitamin D Osteoporosis Study (MAVIDOS) randomized trial, vitamin D supplementation in pregnancy did not lead to greater neonatal bone mass across the trial as a whole, but, in a prespecified secondary analysis by season of birth, led to greater neonatal bone mass among winter-born babies. Demonstrating persistence of this effect into childhood would increase confidence in a long-term benefit of this intervention. We investigated whether antenatal vitamin D supplementation increases offspring bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…The dose of vitamin D recommended for routine use in pregnancy varies internationally, with some advocating 100 μg daily or higher [ 50 ], while the World Health Organization/Food and Agriculture Organization of the United Nations recommends 5 μg daily [ 51 ]; in the UK, it is recommended that pregnant women should consider taking a supplement containing 10 μg between September and March [ 4 ]. In the MAVIDOS randomized trial supplementation, 25 μg of vitamin D daily from 14 weeks gestation until delivery lowered the incidence of infantile atopic eczema [ 5 ] and increased childhood areal bone mineral density in the offspring [ 6 ]. Vitamin D is stored in adipose tissue, and our trial suggests that low dose (10 μg) supplementation over a long period starting preconception can support improved gestational vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose of vitamin D recommended for routine use in pregnancy varies internationally, with some advocating 100 μg daily or higher [ 50 ], while the World Health Organization/Food and Agriculture Organization of the United Nations recommends 5 μg daily [ 51 ]; in the UK, it is recommended that pregnant women should consider taking a supplement containing 10 μg between September and March [ 4 ]. In the MAVIDOS randomized trial supplementation, 25 μg of vitamin D daily from 14 weeks gestation until delivery lowered the incidence of infantile atopic eczema [ 5 ] and increased childhood areal bone mineral density in the offspring [ 6 ]. Vitamin D is stored in adipose tissue, and our trial suggests that low dose (10 μg) supplementation over a long period starting preconception can support improved gestational vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…The principal exception relates to preconception and early pregnancy folic acid supplementation and fortification programs, underpinned by the landmark Medical Research Council trial [ 2 ]. Vitamin D supplementation is also generally recommended, in part based on the recent Maternal Vitamin D Osteoporosis Study (MAVIDOS) trial [ 3 ]; MAVIDOS used a higher dose of vitamin D than is recommended in many settings (25 μg of cholecalciferol daily from early pregnancy until delivery versus 10 μg daily recommended in countries such as the United Kingdom [ 4 ]), which reduced the incidence of infantile atopic eczema in the offspring [ 5 ] and improved measures of bone health in the children at age 4 years [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This, however, would be offset against the reduction in maternal and neonatal morbidity, and thus could be a relatively cheap intervention and warrants further investigation. If these findings and the other identified benefits of higher dose antenatal vitamin D supplementation such as increased offspring bone mass 66 are replicated in further high quality randomized controlled trials without increased risk of harm, consideration should be given to increasing the recommended pregnancy supplementation guidance to 1000 IU/day in the UK. In the interim, promotion of the current guidelines recommending 400 IU/day vitamin D in pregnancy is appropriate to increase the current low uptake of supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Our own metaanalysis of these studies suggested a small positive effect on birth weight and neonatal serum calcium. There are, however, fewer studies that have examined the effect of pregnancy vitamin D supplementation on offspring musculoskeletal parameters; to date, there are 2 published trials assessing neonatal BMD [91,92] and four trials with assessment of BMD in early childhood [93][94][95][96]. The largest published RCT is the MAVIDOS study, which was conducted in three centres in the UK and randomised women with a baseline 25(OH)D of 25-100 nmol/l to either 1000 IU/day cholecalciferol or placebo from 14 to 17 weeks' gestation until delivery [97].…”
Section: Maternal Vitamin D Status In Pregnancy and Offspring Bone He...mentioning
confidence: 99%